Unveiling Symbolism: The Allegorical Tapestry of Female Attire in Poetry and Art of Pakistan - Alia Hadi Ali; Marukh Khan; Aqeel Abbas (Journal of Design and Textiles, 2023)
This research paper sheds light on the representation of traditional women from Punjab and their allegorical representation through Sufi poets and paintings. Women are and continue to be an integral part of art and artistic expression throughout human history from pre-history to modern times. The representation of women as an expression of art is an essential aspect in the history of art. This paper highlights the cultural and traditional depiction of women in the art of Chughtai, Ustad Allah Bux, Amrita Sher Gill and Anna Molka Ahmed through attire and its metaphorical representation. The selected paintings focus on the traditional depiction of Women in Punjab, and provides themes, styles associated in representing the women in paintings of Punjab. Such paintings are very expressive and ideally formalized with great delicacy and devotion, gives importance to womanhood through allegory.The role of females and their interpretation through Sufi poetry explains in visual of painters work choosen as subject matter for explaining. This paper reflects female attire in visuals and poetry. This study is reflecting content analysis of female representation through attire in poetry and painting with context of region Punjab Pakistan.